Current production in a microbial fuel cell using a pure culture of Cupriavidus basilensis growing in acetate or phenol as a carbon source. Issue 4 (10th January 2013) - Friman, Hen; Schechter, Alex; Ioffe, Yulia; Nitzan, Yeshayahu; Cahan, Rivka
Summary A microbial fuel cell (MFC) was operated with a pure culture of Cupriavidus basilensis bacterial cells growing in the anode compartment in a defined medium containing acetate or phenol. Operating this mediator‐less MFC under a constant external resistor of 1 kΩ with acetate or phenol led to current generation of 902 and 310 mA m−2 respectively. In the MFC which was operated using acetate or phenol, the current density measured from the plankton bacterial cells with a fresh electrode was 125 and 109 mA m−2, respectively, whereas the current obtained with biofilm‐covered electrodes in sterile medium was 541 and 228 mA m−2 respectively. After 72 h in the MFC, 86% of the initial phenol concentration was removed, while only 64% was removed after the same time in the control MFC which was held at an open circuit potential (OCP). Furthermore, SEM and confocal microscopy analyses demonstrated a developed biofilm with a live C. basilensis population. In conclusion, in this study we demonstrated, for the first time, use of C. basilensis facultative aerobe bacterial cells in a MFC using acetate or phenol as the sole carbon source which led to electricity generation.